2008
DOI: 10.1113/jphysiol.2008.164004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gene expression and function of uterotonic systems in the rat during gestation, uterine activation and both term and preterm labour

Abstract: We have documented gestation-and labour-(preterm and term) dependent changes in expression of genes encoding contraction associated proteins in the rat uterus and correlated these changes with various parameters of uterine contractility. The data demonstrate increased expression of contractile agonist systems concurrent with decreased expression of relaxant systems after gestational day 20. Significant increases in expression of oxytocin (OT), its receptor (OTR), prostaglandin (PG) H synthase isoform 1 (PGHS-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 69 publications
(84 reference statements)
7
43
2
Order By: Relevance
“…Consistent with the concept of uterine quiescence during the course of pregnancy, we found that oxytocin contraction of myometrium strips was reduced in mid- and late-pregnant rats compared with virgin rats. Some studies have shown that oxytocin contraction of mid-term and late-pregnant uterus is greater than that in non-pregnant uterus, 378 which is opposite from our findings. This is likely because during late pregnancy the uterus is bigger and often thicker, and studies often measure uterine contraction in absolute grams.…”
Section: Mmps and Uterine Contraction During Pregnancy And Laborcontrasting
confidence: 99%
See 1 more Smart Citation
“…Consistent with the concept of uterine quiescence during the course of pregnancy, we found that oxytocin contraction of myometrium strips was reduced in mid- and late-pregnant rats compared with virgin rats. Some studies have shown that oxytocin contraction of mid-term and late-pregnant uterus is greater than that in non-pregnant uterus, 378 which is opposite from our findings. This is likely because during late pregnancy the uterus is bigger and often thicker, and studies often measure uterine contraction in absolute grams.…”
Section: Mmps and Uterine Contraction During Pregnancy And Laborcontrasting
confidence: 99%
“…Consistent with other reports in the rat uterus, 378,402 we have shown that oxytocin causes a steady increase in contraction and an additional spontaneous phasic contractile response. 93 [Ca 2+ ] I is a key regulator of uterine contraction.…”
Section: Mmps and Uterine Contraction During Pregnancy And Laborsupporting
confidence: 93%
“…DHEA and DHEAS production in the fetus is thought to lead to initiation of parturition through their metabolism by the placenta to estrogen [9] , which acts on the myometrium, cervix and fetal membranes. While estrogen is thought to up-regulate the expression of myometrial genes associated with contraction [10] , it is progesterone that is thought to modulate parturition timing through its withdrawal. In a number of animal models, progesterone disappearance from the circulation is associated with onset [11] .…”
Section: The Onset Of Labormentioning
confidence: 99%
“…This leads to the production of pro-inflammatory cytokines and chemokines [33], extravasation of myeloid and lymphoid inflammatory cells (mostly neutrophils and monocytes/macrophages), and eventually, activation of many uterine activation proteins (UAPs). These UAPs promote cervical ripening, fetal membrane weakening, contractions and labor [34][35][36]. Importantly, data show that this inflammatory response does not resolve with birth [16], which may explain the inefficacy of tocolytics at improving neonatal outcomes.…”
Section: Inflammation In Preterm Birthmentioning
confidence: 93%